Aplikasi Probio_FMPlus melalui Air Minum pada Ayam Broiler di Politani Kupang - Hendalia, Ella; Manin, Fahmida; Asra, Revis; Helda, Helda (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2017)
The aims of this study was to reveal the effectiveness of the use of Probio_FMplus broiler. Two hundret of day old chick (DOC) were used in this experiment. DOCs were randomly treated into five treatments with five replications consiting of eight DOCs. Treatments were the use of Probio_FMplus within drinking water of 0, 10, 15 and 20 ml/liter for treatment P0, P1, P2, P3and P4 respectively. The design of experiment was Completely Randomized Design with five treatments and five replications. Parametters measured were ration comsumption, weight gain, slaughter weight and feed conversion. The results of this experiment showed that the level of Probio_FMplus in drinking water did not significantly influence (P>0,05) on ration consumption, weight gain, slaughter weight and feed conversion. It could be concluded that the use of 10 ml/liter of Probio_FMplus in dringking waterwas the most effective in broiler. Kata kunci: probiotik, prebiotik, simbiotik, putak